Projeto e prototipagem de sistema para aquisição e análise de EMG do assoalho pélvico - Souza, Diogo; Fonseca, Lucas; Melo, Julio; Cury, Alethea; Viana, Elizabel; Correa, Edgard (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
Electromyography (EMG) is one of the methods used to measure the muscular activity, it can be done via external electrodes or using needles. Nowadays the EMG is used in many areas as medicine, physiotherapy, odontology, phonoaudiology and even to create prosthetic limbs. This technology is used by physiotherapists to evaluate the activity of specific muscles. A specific example is the evaluation of muscles on the Pelvic Floor, field covering the evaluation and treatment of this set of muscles. Most of these evaluation techniques require that the patient be on still positions, since the measurement device is physically wired to the data analysis system. To mitigate this problem our work shows the development of a Wearable Pelvic Floor EMG evaluation system that transmits the data wirelessly to the data analysis system, allowing the patient to be evaluated in more natural positions such as running, crouching and others. This paper covers the development process of the device and dada analysis software, resulting in a system that is ready to clinical tests by the end of the year.